Formulation and analysis of physical properties of Turi leaf extract suspension (Sesbania grandiflora L.) - Wilda Amananti; ‪Rosaria Ika Pratiwi‬ (Journal of Natural Sciences and Mathematics Research, 2023)
Sesbania Grandiflora .L is a type of plant that has so many benefits in the treatment of various kinds Diseases include laxatives, pain relievers (analgesics), fever reducers (antipyretic), laxative urine (diuretic), and others. Almost all parts of This plant belonging to the genus Sesbania Grandiflora is efficacious as a medicine covering the skin stems, flowers, leaves and roots. Sesbania Grandiflora .L contains alkaloid compounds, glycosides, flavonoids, saponins, tannins and phenols which give a positive reaction in the phytochemical screening assay. Turi leaf extract need to be made in the form of pharmaceutical dosage forms for ease of use. One preparation that can be applied is a suspension.In this study, turi leaf extract was used as the active substance. The suspension was made in 3 formulas with different concentrations of turi leaf extract. The finished suspension was tested for physical characteristics including organoleptic test, homogeneity test, pH test, density test and viscosity test.Based on the results of secondary metabolite tests, turi leaves contain alkaloids, flavonoids, tannins and saponins. Based on the results of testing the physical properties of the suspension, it showed that all formulas met SNI standards based on organoleptic, homogeneity, pH and density tests. while based on the viscosity test the suspension made does not meet SNI standards.